1993
DOI: 10.1177/0272989x9301300408
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Diagnostic Accuracy from Multiple Conflicting Reports

Abstract: Reports of diagnostic accuracy often differ. The authors present a method to summarize disparate reports that uses a logistic transformation and linear regression to produce a summary receiver operating characteristic curve. The curve is useful for summarizing a body of diagnostic accuracy literature, comparing technologies, detecting outliers, and finding the optimum operating point of the test. Examples from clinical chemistry and diagnostic radiology are provided. By extending the logic of meta-analysis to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
284
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(286 citation statements)
references
References 10 publications
0
284
0
2
Order By: Relevance
“…Given that in diagnostic test studies it is very common that the variability of results does not result merely from chance, since variability may be explicitly or implicitly caused by variation of the cut-off point, the variability estimates provided by the random effects model are particularly important 10 . Using random effects methods more frequently, the forms of metaanalysis of studies on diagnostic tests or prognostic factors are shown in Table 3.…”
Section: Calculate the Results By Means Of Metaanalysis Estimating Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that in diagnostic test studies it is very common that the variability of results does not result merely from chance, since variability may be explicitly or implicitly caused by variation of the cut-off point, the variability estimates provided by the random effects model are particularly important 10 . Using random effects methods more frequently, the forms of metaanalysis of studies on diagnostic tests or prognostic factors are shown in Table 3.…”
Section: Calculate the Results By Means Of Metaanalysis Estimating Dmentioning
confidence: 99%
“…Meta-analyses of studies on prognostic factors or diagnostic tests, in turn, face different challenges, such as different cut-off points for the positive or negative result of a test, or assessment of tests that were performed in prospective studies for the analysis of therapeutic interventions. In the 1990's, new statistical techniques of combination of studies on diagnostic tests were developed [9][10][11] . Since 1994, when a guideline for meta-analysis of studies on diagnostic tests 12 was published, several different publications with criticisms and propositions on specific aspects of each stage of the process came up.…”
Section: Introductionmentioning
confidence: 99%
“…Publication bias was assessed by Begg s and Egger s tests 13 . To avoid undefined values that would have arisen due to zero values, 0.5 was added to any zero cell 14 . Statistical signi cance was set at P 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…The summary receiver operating characteristic (SROC) method, introduced by Littenberg and Moses [2,3], has been widely used by authors of published meta-analyses that examine diagnostic test accuracy. However, the SROC method has some inherent limitations that could affect its validity and usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…true positives (TP), false positives (FP), true negatives (TN), and false negatives (FN). The continuity correction method, i.e., adding one half to each count in calculating the true-positive rate and the false-positive rate, introduces non-negligible downward bias to the estimated SROC curve [2,3,4]. An additional problem with the SROC method is that confidence intervals are based on large sample theory approximations and the appropriate sample size for a meta-analysis is the number of studies which may not be large enough for the approximation to be accurate.…”
Section: Introductionmentioning
confidence: 99%